(untitled) (ENTHYMEMA, 2014)
The paper is focused around two biographical themes. Theme one is history of demolishing Leningrad school of dramatic theory developed in the State Institute of History of Art (GIII) in the 1920s. In 1931, the GIII was closed by a Sovnarkom resolution and transformed into Len- ingrad division of the State Academy of Art Studies (LOGAIS) established by the same resolu- tion. Theme two is description of the ‘academic traumatism’, traumatic behavior and its bio- graphical effects caused by destruction of a whole scientific trend during the anti-formalism campaign of the early 1930s. Based on archival documents (from the Russian State Archive of Literature and Art), shorthand notes and reports on discussions of the 1930s, we analyze behav- ioral tactics of initiators, participants and victims of the longstanding stigmatization and catalog absolutory, denunciative and repentant narratives. In particular, this paper analyzes the un- published letter to the editors of Rabochiy i Teatr journal written by Alexander Slonimsky, one of the key players in development and obliteration of dramatic theory associated primarily with Alexei Gvozdev’s group and with transformation and dissolution of the leading humanities in- stitutes. The text of the letter appears to be engrained in the complicated mosaic of measures aimed to discredit Meyerhold’s theater practice and Gvozdev as the leader of the scientific school. Deliberate misinterpretation and corruption of self-descriptions along with reconstruc- tion of biographies are some of the most crucial factors that affected reception of cultural pro- jects and their creators in the 1930s and later.